Struktur Komunitas Makrozoobenthos di Ekosistem Air Tawar Sungai Mencerit, Lombok Timur Berbasis Etnoekologi - Fadila Anggita Putri; Nurlita Lestariani; Tia Haerani; Angga Raditya (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to analyze the structure of macrobenthos communities in the freshwater ecosystem of the Mencerit River, East Lombok based on an ethnoecological approach. The study used a quantitative descriptive method with an ethnoecological approach through direct observation and interviews with local communities. Sampling was carried out at four observation stations using a purposive sampling method with three replications at each station. The data collected included the type and number of macrobenthos, water quality parameters, and the results of interviews with the community regarding river conditions and the presence of aquatic fauna. The results showed that 173 macrobenthos individuals were found with a total abundance of 14.42 individuals/m² consisting of 9 species, with the dominant species being Pomacea canaliculata, Radix rubiginosa, and Tarebia granifera. The diversity index (H’) value of 1.98 is classified as moderate, while the dominance index (C) of 0.17 indicates low dominance, so the condition of the river ecosystem is still relatively stable. The EPT value of 2 and the EPT ratio of 13.87 indicate that the water quality is still quite good. The conclusions of this study indicate that the Mencerit River ecosystem is relatively stable with good water quality, supported by the high level of ecological knowledge of the local community in maintaining the sustainability of the aquatic environment through traditional practices.